2009
DOI: 10.1089/ten.tec.2008.0323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viral and Nonviral Vectors for Gene Transfer to Human Endothelial Progenitor Cells

Abstract: We have found adenovirus to be the most efficient of the vector systems tested for gene delivery to EPCs, an effect that is mediated almost entirely by one of two identified subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Based thereon, we were able to obtain much higher transduction rates for lentiviral vectors (up to 99%) than those described by Kealy et al [17] at lower MOIs. Even with retroviral vectors, transduction rates were above 70%, that is, comparable with those seen with adenoviral vectors.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Based thereon, we were able to obtain much higher transduction rates for lentiviral vectors (up to 99%) than those described by Kealy et al [17] at lower MOIs. Even with retroviral vectors, transduction rates were above 70%, that is, comparable with those seen with adenoviral vectors.…”
Section: Discussionsupporting
confidence: 51%
“…As shown by Kealy et al [17], genetic modification with adenoviral vectors did not change the functional capabilities of EPCs. Different groups have introduced Equal amounts of amplified RNA from endothelial progenitor cells (EPCs) and freshly isolated mononuclear cells (MNCs) were labeled with Cy5 and Cy3 and hybridized to a PIQOR Stem Cell microarray.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, adenoviral vectors have the capability of efficiently transducing endothelial progenitor cells. The efficiency of delivering the green fluorescent protein (GFP) reporter gene using an adenoviral vector was 80%, but only up to 35% using liposomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal gene delivery method for a given therapy will be dependant on tissue location, and type, as well as therapeutic strategy. While certain studies have been reported comparing the efficiencies from different vectors (Wang, A. Y. et al 2004;Kealy et al 2009), given the paucity of information regards direct comparisons between various delivery techniques, especially in the cancer setting, this study assesses the level and duration of reporter gene expression within target murine tissues when delivered by a range of commonly used gene delivery techniques; electroporation, sonoporation, lipofection, Adenovirus and Adeno-Associated Virus.…”
mentioning
confidence: 99%